Комп’ютерний зір в епоху штучного інтелекту: переосмислення освітніх підходів та методологій - Кит, М. О. (ХНУРЕ, 2024)
This paper delves into the integration of Artificial Intelligence (AI) [1] in Computer Vision (CV) [2] education, highlighting the shift towards incorporating advanced computational techniques like deep learning. It critiques traditional CV courses for their reliance on outdated methodologies and lack of practical engagement, proposing a Python-based curriculum with OpenCV, scikit-learn, TensorFlow, and PyTorch. This curriculum comprises five modules that cover the fundamentals, image processing, object recognition, and image segmentation, culminating in practical assignments. The revamped approach aims to prepare students for contemporary CV challenges, emphasizing the importance of aligning educational practices with technological advancements to equip the next generation of CV experts with the skills required for innovation and practical application in the field.
Keywords: комп'ютерний зір; штучний інтелект